Kinetics of the Antibody Response to Symptomatic SARS-CoV-2 Infection in Vaccinated and Unvaccinated Individuals in the Blinded Phase of the mRNA-1273 COVID-19 Vaccine Efficacy Trial. (13th February 2023) - Follmann, Dean; Janes, Holly E; Chu, Eric; Jayashankar, Lakshmi; Petropoulos, Christos J; Serebryannyy, Leonid; Carroll, Robin; Jean-Baptiste, Naz; Narpala, Sandeep; Lin, Bob C; McDermott, Adrian; Novak, Richard M; et al.
Abstract: Background: Hybrid immunity is associated with more durable protection against coronavirus disease 2019 (COVID-19). We describe the antibody responses following severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in vaccinated and unvaccinated individuals. Methods: The 55 vaccine arm COVID-19 cases diagnosed during the blinded phase of the Coronavirus Efficacy trial were matched with 55 placebo arm COVID-19 cases. Pseudovirus neutralizing antibody (nAb) activity to the ancestral strain and binding antibody (bAb) responses to nucleocapsid and spike antigens (ancestral and variants of concern [VOCs]) were assessed on disease day 1 (DD1) and 28 days later (DD29). Results: The primary analysis set was 46 vaccine cases and 49 placebo cases with COVID-19 at least 57 days post–first dose. For vaccine group cases, there was a 1.88-fold rise in ancestral antispike bAbs 1 month post–disease onset, although 47% had no increase. The vaccine-to-placebo geometric mean ratios for DD29 antispike and antinucleocapsid bAbs were 6.9 and 0.04, respectively. DD29 mean bAb levels were higher for vaccine vs placebo cases for all VOCs. DD1 nasal viral load positively correlated with bAb levels in the vaccine group. Conclusions: Following COVID-19, vaccinated participants had higher levels and greater breadth of antispike bAbs and higher nAb titers than unvaccinated participants. These were largely attributable to the primary immunization series. Abstract : Following disease, the previously vaccinated have a more potent and broader response to spike compared to unvaccinated disease cases. Roughly half of the vaccinated cases show minimal immune response to disease.